ASOCIACIÓN EMPRESARIAL MEDIANTE CLUSTERS, EL CASO ESPECÍFICO DE BAHÍA DE BANDERAS, NAYARIT - Tania Nadiezhda Plascencia Cuevas; Alma Rosa Malacara Castillo (European Scientific Journal, ESJ, 2015)
Mexico has several successful and globally recognized business associations, however, be noted that these cases are concentrated mainly in the Midwest. Ideally, this strategy could be raised and developed in each of the states of Mexico, analyzing the strengths and opportunities of each entity. Does the state of Nayarit have a positive experience in this topic? What are the opportunities to be developed for the implementation of this model? The present study shows a descriptive analysis of the clusters established in the municipality of Bahia de Banderas, Nayarit, public policy and improvement alternatives that contribute to increased productivity and competitiveness of the micro, small and medium enterprises (MSMEs). Being a town just starting to implement such strategies for local economic development, it is concluded in the first instance the need to create an information system to collect specific information on the results of the clusters, even though they exist, they have not been given the necessary formalities to be evaluated.